A data aggregation scheme for boundary detection and tracking of continuous objects in WSN. Issue 1 (2nd January 2017) - Lee, Hyun-Jung; Soe, Myat Thida; Chauhdary, Sajjad Hussain; Rhee, Soyeon; Park, Myong-Soon
Abstract: Efficient and accurate detection and tracking of continuous objects such as fire and hazardous bio-chemical material diffusion requires an extensive communication between nodes in wireless sensor networks. In this paper, we propose an efficient algorithm that monitors a moving object by selecting a subset of monitoring data of object boundary nodes. The proposed algorithm uses a Data Aggregation method to reduce the number of report messages and a piecewise Quadratic Polynomial Interpolation algorithm to find the boundary points precisely. Simulation results show that the proposed scheme significantly reduces the number of report messages to the sink node and also improves boundary accuracy.